A Survey on White Box Cryptography Model for Mobile Payment Systems - Aydın, Muhammed Ali; Sertbaş, Ahmet; ŞENGEL, ÖZNUR (My University, 2017)
The technology is showing rapid development and these developments are changing our lives, our habits, and our needs. As electronic devices, which are indispensable for our daily lives, continue to be intelligent, we are able to do our every operation through these devices. Mobile payment technologies and services are one of the innovations. Consumers all over the world and in our country have started to use their mobile devices as a means of payment as well as communication services. With rapidly developing technology, one of the most important needs of many systems such as electronic, mobile and bank is to move and store the data safely. In addition to data security in electronic transactions, the speed of the system operations is becoming very important. Developing a mobile payment system whether by installing an application or using existing hardware, the most important issue in both cases is the creation of a reliable system based on the protection of the current situation of the consumer and the confidentiality of their information.
Keywords: Mobile payment; Cryptography; Cryptography model; White box cryptography; Data security